The Development of quest learning activities with webquest on human rights, Mathayom 4 - Khoturapun, Atittaya; Rittidet, Prasopsuk; Laosuwan, Tatchavat (Journal for Developing the Social and Community, 2023)
This research was aimed to ; (1) development of quest learning activities with webquest on human rights, Mathayom 4. ; (2) compare the learning achievement before and after learning by quest learning activities with webquest on human rights, Mathayom 4. ; (3) compare the Attributes wanting to learng by using quest learning activities with webquest before and after of Mathayom 4. ; (4) compare the student satisfaction on the quest learning activities with webquest of Mathayom 4. The research sample was consisted of 42 Mathayom 4 students, obtained through the cluster random sampling technique. The instruments used for this research included the activities lesson plan, Attributes wanting to learng questionnaire and learning satisfaction questionnaire. The statistics for data analysis were mean, standard deviation, and t - test (Dependent samples) The findings were as follows ; (1) the development of quest learning activities with webquest on human rights is suitable in the most suitable criteria. ; (2) the learning achievement with quest learning activities with webquest was higher than before learning at .05 level of significance. ; (3) the Attributes wanting to learng ability of students who receive the quest learning activities with webquest was higher than before learning and ; (4) the student’ satisfaction on the quest learning activities with webquest was at a high level.